Answer:40c^2-46c -14
Step-by-step explanation:
(8c+2)*(5c-7)
8c*(5c-7)+2(5c-7)
40c^2-56c+10c-14
40c^2-46c-14
Applying the division rule of exponents, 6^10/6^6 can be rewritten in the form of b^n as: 6^10/6^6 = 6^4.
<h3>What is the Division Rule of Exponents?</h3>
The division rule of exponents state that if we have a numerator and a denominator with the same base, the quotient will be the base, while we subtract the exponent value of the denominator from the exponent value of the numerator.
For example, if we have, a³/a², the division rule of exponents states that:
a^(3 - 2) = a^1 = a.
Given the expression, 6^10/6^6, we can rewrite the expression in the form of b^n by applying the division rule of exponents as shown below:
6^10/6^6 = 6^(10 - 6)
6^10/6^6 = 6^4
In conclusion, applying the division rule of exponents, 6^10/6^6 can be rewritten in the form of b^n as: 6^10/6^6 = 6^4.
Learn more about the division rule of exponents on:
brainly.com/question/2263967
#SPJ1
The endpoints of a diameter of a circle are (4,-2) and (3,6). The area of the circle in terms of pi is 65pi
First, is to get the length of the diameter by getting the distance of the two points: (4, -2) and (3, 6)
dis = sqrt( (x2-x1)^2 + (y2-y1)^2)
dis = sqrt( (3-4)^2 + (6--2)^2 )
dis = sqrt( 1 + 64 )
dis = sqrt(65)
Next, is to find the area of the circle:
A = pi * r^2
A = pi * (sqrt(65))^2
A = 204.20 square units
<span>6.16×10^6
10^6 = </span>10000006.16 x 1000000 = <span>6160000
</span><span>6,160,000 is your answer
</span>
hope this helps
Answer:
76/48
19/12
19/12
Step-by-step explanation:
19/12.